Management control systems in Madeira island largest firms: Evidence on the balanced scorecard usage - Curado, Carla; Manica, José (Journal of Business Economics and Management, 2010)
This paper describes the findings of an exploratory study on the use of management control systems in Madeira Island providing evidence on the Balanced Scorecard (BSC) usage. Empirical data collected illustrates the degree of BSC usage at the Island’s biggest corporations and provides response to the research questions. The findings reveal remarkable differences concerning management control systems’ use across corporations in the study and previous research reports from other regions. Finally, this study discusses managerial implications and includes invitations to future research directions. Valdymo sistema Madeiros salos didžiosiose įmonėse: rezultatų apskaitos sistemos naudojimo pavyzdžiu Santrauka. Straipsnyje pateikiami duomenys apie mokslinį valdymo kontrolės sistemų tyrimą, atliktą Madeiros saloje naudojant subalansuotos apskaitos duomenis. Surinkti empiriniai duomenys rodo naudojimąsi subalansuotos apskaitos modeliu didžiausiose salos korporacijose ir pateikia atsakymus į tyrimo klausimus. Tyrimo duomenys atskleidžia svarbius skirtumus tarp valdymo kontrolės sistemų naudojimo įvairiose įmonėse, lyginant kitų regionų ankstesnių tyrimų ataskaitas. Šiame tyrime aptariama organizacijų vadybos reikšmė, kviečiama aptarti būsimų mokslinių tyrimų kryptis. Reikšminiai žodžiai: valdymo sistemos, darni apskaita, didelės įmonės, empirinis tyrimas. First Published Online: 10 Feb 2011